Staff Welfare Practices Adopted by Principals for Improved Teacher’s Job Performance in Public Secondary Schools in Otuocha Education Zone, Anambra State. (UNIZIK Journal of Educational Management and Policy, 2026)
The study investigated the staff welfare practices adopted by principals for improved teachers’job performance in public secondary schools in Otuocha Education Zone, Anambra State. Oneresearch question guided the study. The study adopted a descriptive survey research design. Thepopulation of the study comprised 545 respondents made up of 26 principals and 519 teachersfrom 26 public secondary schools in the study area. A sample size of 140 respondents wasselected using simple random sampling technique. The instrument used for data collection was astructured questionnaire titled “Principals’ Staff Welfare Practices Questionnaire (PSWPQ).”The instrument was validated by three experts in Educational Management and Measurementand Evaluation, while the reliability of the instrument was established using Cronbach Alphamethod which yielded a reliability coefficient of 0.81, indicating that the instrument was reliable.Data collected were analyzed using mean and standard deviation. The findings revealed amongothers that principals adopted several staff welfare practices such as encouraging teachers,involving them in decision-making and goal-setting.. Based on the findings, the studyrecommended among others that principals should continue to promote staff welfare throughmotivation, participation in school administration, and support for teachers’ professionaldevelopment programmes such as workshops and seminars to improve teachers’ job performance.
Keywords: Staff Welfare Practices, Teachers’ Job Performance